Interpretations of Luxury Exploring the Consumer Perspective - Turunen, Linda Lisa Maria (Palgrave Advances in Luxury,, 2018)
Exploring the elements that constitute the perceived luxuriousness of a brand, this book addresses the changing definitions of the term 'luxury' in today's world. Taking the approach that the concept of luxury evolves from the consumer, the author introduces a conceptual model which explains how the consumer interprets the luxuriousness of a brand. This innovative study analyses the key elements that influence luxury branding, such as extended product, perceived uniqueness, authenticity and context specificity. By critically reflecting on the existing definitions of luxury and its challenges, this book makes a unique contribution to research and an essential read for marketing students and scholars.